The Development of Hypermedia-Based E-Module to Enhance Students' Creative Thinking Skills in the Topic of Digestive System for Junior High School Students (SMP/MTs) - Mohamad Khoirul Anam; Imam Mudakir; Jekti Prihatin (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
The education system in Indonesia has undergone changes due to several factors such as 21st century education trends and the impact of the COVID-19 pandemic. These changes have resulted in a shift in student learning behavior towards different learning styles. With the end of the pandemic, students have returned to face-to-face learning, leading to the loss of certain learning behaviors adopted during the pandemic period. This, may result in a decrease in students' thinking ability. The purpose of this study is to develop hypermedia-based e-modules to improve students' creative thinking skills. The method used in this research is the Research and Development (R&D) method. This method follows the ADDIE model which consists of analysis, design, development, implementation, and evaluation. The development in this research includes hypermedia-based e-modules, learning instruments, creative thinking tests. The validity of the hypermedia-based e-module was assessed using the results of media validation. Effectiveness was measured by analyzing student and teacher responses. Effectiveness was determined through pre-test and post-test methods for creative thinking tests. The validation results showed